Preclinical mouse solid tumour models: status quo, challenges and perspectives - Gengenbacher, Nicolas; Singhal, Mahak; Augustin, Hellmut (Nature reviews. Cancer, 2017)
Oncology research in humans is limited to analytical and observational studies for obvious ethical reasons, with therapy-focused clinical trials being the one exception to this rule. Preclinical mouse tumour models therefore serve as an indispensable intermediate experimental model system bridging more reductionist in vitro research with human studies. Based on a systematic survey of preclinical mouse tumour studies published in eight scientific journals in 2016, this Analysis provides an overview of how contemporary preclinical mouse tumour biology research is pursued. It thereby identifies some of the most important challenges in this field and discusses potential ways in which preclinical mouse tumour models could be improved for better relevance, reproducibility and translatability.